2021
DOI: 10.46606/eajess2021v02i02.0073
|View full text |Cite
|
Sign up to set email alerts
|

Availability of ICT Facilities and Teachers’ Competence in the Use of ICT among Public Secondary Schools in Ngara District, Tanzania

Abstract: This study sought to establish the availability of ICT facilities and teachers competence in the use of ICT among public secondary schools in Ngara, Tanzania. The study employed a mixed research approach in that interview schedule and questionnaire were employed as sources of data. The population of the study was 525 stakeholders from 31 secondary schools, including the DEO, the WEO, the Heads of schools, ICT manager and teachers. Simple random sampling and purposive sampling were used to determine the sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This inevitability, on the other hand, does not rule out other options for dealing with our current impediments. The present requirement has its own set of challenges (Fidelis & Onyango, 2021). Therefore, dealing with the current situation, as well as future unforeseeable contingencies, will require realistic and proactive efforts to lessen the detrimental effects of future disasters.…”
Section: Recognizing the Impact Of Covid-19 On Online Education And E...mentioning
confidence: 99%
See 2 more Smart Citations
“…This inevitability, on the other hand, does not rule out other options for dealing with our current impediments. The present requirement has its own set of challenges (Fidelis & Onyango, 2021). Therefore, dealing with the current situation, as well as future unforeseeable contingencies, will require realistic and proactive efforts to lessen the detrimental effects of future disasters.…”
Section: Recognizing the Impact Of Covid-19 On Online Education And E...mentioning
confidence: 99%
“…These are in line with the idea that teachers should be trained in developing pedagogical approaches so that they can improve the ICT abilities and work with digital technology (Cabero-Almenara & Llorente-Cejudo, 2020). The existing mandate, on the other hand, has its own set of issues (Fidelis & Onyango, 2021). As a result, dealing with the current situation, as well as future unforeseeable contingencies, will require realistic and proactive efforts to lessen the detrimental effects of future disasters.…”
Section: Other Propositions Are As Followsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several studies on availability and utilization of ICTs in higher education institutions have found that ICT facilities are limited in most of education institutions (Onu & Ezhim, 2019;Fidelis & Onyango, 2021). Other studies proclaim that ICT facilities are available but they are not properly utilized by members of academic staff during teaching and learning processes (Kiboss & Kosewe, 2017;Okorieocha et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…ICT facilities have devices used to support teaching and learning (Fidelis & Onyango, 2021). ICT facilitates not only the delivery of teaching content but also the learning process itself (Tarus et al, 2015).…”
Section: Introductionmentioning
confidence: 99%